2004
DOI: 10.1128/jb.186.7.1983-1990.2004
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of σEon Compartmentalization of σFActivity during Sporulation ofBacillus subtilis

Abstract: Spore formation by Bacillus subtilis is a primitive form of development. In response to nutrient starvation and high cell density, B. subtilis divides asymmetrically, resulting in two cells with different sizes and cell fates. Immediately after division, the transcription factor F becomes active in the smaller prespore, which is followed by the activation of E in the larger mother cell. In this report, we examine the role of the mother cell-specific transcription factor E in maintaining the compartmentalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…However, a separate study found that ␤-galactosidase could not diffuse across the septa of class II mutants and proposed that persistence of SpoIIE in the mother cell rather than a hole in the septum was responsible for the loss of compartmentalization (234). Our recent studies support the existence of a small hole permeable to factors or their regulators and to GFP (110).…”
Section: Disruption Of Compartmentalizationsupporting
confidence: 81%
See 1 more Smart Citation
“…However, a separate study found that ␤-galactosidase could not diffuse across the septa of class II mutants and proposed that persistence of SpoIIE in the mother cell rather than a hole in the septum was responsible for the loss of compartmentalization (234). Our recent studies support the existence of a small hole permeable to factors or their regulators and to GFP (110).…”
Section: Disruption Of Compartmentalizationsupporting
confidence: 81%
“…Given that E -directed genes are required to cause septal wall autolysis during engulfment (1,37,57,85,228,232,246,271,272), it seemed plausible that similar activity might enlarge a breach in the septum resulting from loss of SpoIIIE. Indeed, E -directed transcription of spoIID and spoIIP is required to disrupt compartmentalization in spoIIIE class II mutants (110). Presumably, autolytic activity associated with SpoIID and SpoIIP enlarges the putative hole sufficiently to allow passage of F or its regulators and of GFP and possibly of E .…”
Section: Disruption Of Compartmentalizationmentioning
confidence: 99%
“…Such protein fluorophores exhibit great utility in studying protein localization and gene expression during sporulation, specifically in Bacillus spp. (Asai et al, 2001;Hilbert et al, 2004;McBride et al, 2005). Green fluorescent protein and its analogues require oxygen for maturation and subsequent fluorescence (Reid and Flynn, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The SpoIIIE protein localizes to the middle of the sporulation division septum (38,48). It forms an effective seal around the DNA during translocation, preventing the diffusion of proteins between the prespore and mother cell (16,48). During engulfment, it migrates with the engulfing membrane to the cell pole, where it is required for completion of engulfment (38).…”
mentioning
confidence: 99%